(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
This conversation with the Peruvian writer took place in December 1997 in Berlin. At first, I did not think about publishing it; I only used it in lectures or discussions with friends. When I presented it in a literature class at the University of Los Lagos in Osorno, Chile (2001), a colleague suggested that I publish it because, he found it very interesting to get to know the great novelist better. His arguments convinced me, so I started transcribing this dialogue, occasionally changing a minor detail to facilitate a better reading of the spontaneous and informal conversation at Vargas Llosa’s Berlin home.